KODE BAHASA DALAM INTERAKSI SOSIAL SANTRE KAJIAN SOSIOLINGUISTIK DI PESANTREN BANYUMAS - Rokhman, Fathur (LITERA, 2015)
<img src="data:image/png;base64,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